THE EFFECT OF AUDIO VISUAL MEDIA, PARENTS’ PARTICIPATION, AND LEARNING MOTIVATION DURING THE COVID-19 PANDEMIC ON LEARNING ACHIEVEMENT - Muhammad Fajar Kurniawan; Sutiah; Endah K. Purwaningtyas (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Learning in Indonesia is conducted by applying the classical system, also known as face-to-face learning. However, during the COVID-19 pandemic, everyone was required to shift to online learning, including in elementary schools. This research utilized a quantitative approach, specifically a quantitative correlational method. The samples were collected using the Problem Examination procedure with a regular randomized examination strategy (Methodical Irregular Examining). From a population of 160 students, 32 samples were obtained. The results of this study showed that: (1) The mean scores obtained were 3.94, 3.91, and 3.94; (2) Parental participation had a direct effect on students’ learning achievement in Kecamatan Singkut, with a score of 6.013 > 2.048, indicating a significant influence of parental participation on learning achievement; and (3) Audio-visual media, parental participation, and learning motivation contributed 57.8% to learning achievement, based on the effective contribution value of each variable used in the study, while the remaining 42.2% was influenced by other variables not included in this research.